Precise temporal dynamics of ripple events support order memory in human hippocampal–cortical circuits - Sarah Seger; Erdogan Ergit; Sruja Arya; Brad Lega (Proceedings of the National Academy of Sciences, 2025)
Serial order memory, a key type of episodic representation, requires the encoding of map–like context information (interitem relationships) to facilitate recall. In rodent models, both spatial and nonspatial order memory depend heavily on the hippocampus. However, in humans, lesional and neurophysiological data also implicate extrahippocampal areas, especially the orbital frontal cortex and medial parietal regions, in these mnemonic abilities. To investigate the neurophysiological mechanisms of order information in human memory, we used direct brain recordings from hippocampal–cortical circuits as neurosurgical patients performed a serial recall task. Our unique dataset included simultaneous acquisition of data from the hippocampus, orbitofrontal cortex, and posterior cingulate regions. Focusing on ripple events, we demonstrate distinct interregional dynamics during successful order memory encoding using temporally precise, simultaneous recordings across these circuits. The relative timing of co-rippling events implicates theta oscillations in cross-regional integration, particularly between the hippocampus and PCC, and we show that ripple rate, but not ripple duration, is correlated with the quantity of encoded order information. Notably, we find evidence for theta phase coding of serial position for early list items. We link our findings with computational and anatomical models of episodic memory processing as well as general theories of temporal binding facilitated by co-rippling events. These results point toward complementary mechanisms for order representation across hippocampal circuits and suggest the potential of anatomically specific approaches for neuromodulation that alter mnemonic neurophysiology.